(3TQM ZQjH GdSjQI GdfHhjIs - (3CHh PQ Hf eMeO Hf eSYhO GdNTfs; (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s ((3CMeO Hf MSf Hf eMeO GdCfUGQi s)
(3ChdgG (B:s
(3bGd GdTjN Gdabjg GdNTf QVi Gddg Yfg (B: (3GdMeO ddg HGYK GdQSd hHYO agPG EedGA CedjJg cJGH SjQI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hGdeHGPd (B: (3LeY eHPd , hgh GdKhH GdPi jJHPd ajg hGdUGOi (B: (3GdYGWT GfJgi GdLR AGdehai YTQjf hHJeGeg Ke LejY GdcJGH s
(3GdfSNI ebGHdI Ydi fSNI SeYJ Ydi GdeUfa SfI (B603 (3hYdjgG eYGQVI CNQi JGQjNgG (B641s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs